Digitale Übersetzungsprogramme und Online-Wörterbücher im Fremdsprachenunterricht: : Erkenntnisse aus einer Umfrage bei Lehrpersonen und Lernenden der obligatorischen, post-obligatorischen und tertiären Bildung - Udry, Isabelle; Berthele, Raphael (Linguistik Online, 2023)
This survey investigates teacher and student perceptions and beliefs relating to the use of digital translation tools and online dictionaries (e. g. Google Translate, DeepL, Leo, Pons) in the foreign language classroom. Over the past few years, these tools have become increasingly popular, a development that has given rise to questions about their benefits for foreign language learning and teaching. A total of 1187 participants (985 students and 202 teachers) took part in the study. They came from primary schools, lower and upper secondary schools (Gymnasium and Fachmatura, vocational schools), as well as tertiary education and professional development classes. The survey was conducted in French (n=834) and German (n=353) in the cantons of Bern, Fribourg, Geneva, Jura, Neuchâtel and Solothurn. Participation was voluntary. Results show that regardless of language background and educational context, participants perceive of the tools as a normal and largely established part of their everyday practices. Compared to their teachers, students are more optimistic about the tools’ potential contribution to foreign language learning and less concerned about possible pitfalls linked to using the tools. Students in lower secondary school use digital translation aids less frequently and rate their contribution to language learning and motivation less favourably than the other learner groups. Many teachers would like to use digital translators and online dictionaries in their classroom, but they express uncertainty about how to do so meaningfully. Teachers voice concerns over certain student practices, namely the lack of cognitive involvement when simply translating text without considering the output. Teachers also highlight the gap between curricular/institutional prescriptions and the way the tools are commonly used, a mismatch that can affect their teaching. Overall, our findings emphasize the need for a) empirical evidence on the effects of digital translation tools on foreign language acquisition, b) pedagogical scenarios for implementing the tools, and 3) alignment of policy with practice.